MEMBANGUN SPIRITUALITAS BERDASARKAN SURAT 1 TIMOTIUS 4:12 - Manase Gulo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2014)
Life in this day and age is shaped by various elements that influence one another, so that each person becomes a unique person. Influence comes from family background, social culture, economic factors and bad habits, depending on the environment in which a person lives. Paul wanted to talk to them as spiritual people, but he found that they were still